Symptom attribution and risk perception in individuals with idiopathic environmental intolerance to electromagnetic fields and in the general population. (May 2014) - van Dongen, Diana; Smid, Tjabe; Timmermans, Daniëlle RM
Aim: To investigate differences in health perception and electromagnetic fields (EMF) between people within the general population reporting sensitivity or non-sensitivity to EMF, and people who registered themselves as sensitive to EMF at a non-governmental organisation (NGO). Methods: Correlations and regression analysis to compare a sample of the general population recruited via internet panel to individuals with idiopathic environmental intolerance to EMF (IEI-EMF) recruited via an interest group. Results: The general population sensitive group was more similar to the non-sensitive group in personal characteristics than to the NGO sensitive group. They experienced more – and more frequent – non-specific symptoms, reported higher perceived risk of EMF, and attributed their symptoms more to EMF than the non-sensitive group, but less than the NGO sensitive group. There was a positive association between attribution of symptoms to EMF and reported intensity of non-specific symptoms, which was stronger for the NGO sensitive subjects than for the general population. Conclusions: People sensitive to EMF and recruited via an internet panel differ from people sensitive to EMF and recruited via an NGO, who reported a higher frequency of non-specific symptoms. Attribution of symptoms to EMF is one of the predictors of the intensity of physical symptoms. Changing the perceived association between EMF and health problems in individuals with IEI-EMF might contribute to a better health experience.